2007
DOI: 10.1038/sj.gene.6364433
|View full text |Cite
|
Sign up to set email alerts
|

Associations of killer cell immunoglobulin-like receptor genes with complications of rheumatoid arthritis

Abstract: We investigated whether killer cell immunoglobulin-like receptor (KIR) genes are risk factor(s) for rheumatoid arthritis (RA) and its clinical manifestations. One hundred and seventy-seven RA patients and 243 healthy individuals were tested for the presence of 11 KIR genes using PCR-SSP method. The frequencies of KIRs in patients with RA were similar to the frequencies in controls. However, RA patients positive for KIR2DL3 and negative for KIR2DS3 had earlier disease diagnosis. Additionally, KIR2DL2 and KIR2DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
3
35
1
1
Order By: Relevance
“…HWE test was performed on genotype distribution of the control groups, only one [34] of them showed p > 0.05 in HWE, other articles could not be tested because of the lack of raw data. Six [14,20,31,32,34,35] of the nine studies were of high quality (NOS score P 7) and the other three scored six and are shown in Table 1.…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…HWE test was performed on genotype distribution of the control groups, only one [34] of them showed p > 0.05 in HWE, other articles could not be tested because of the lack of raw data. Six [14,20,31,32,34,35] of the nine studies were of high quality (NOS score P 7) and the other three scored six and are shown in Table 1.…”
Section: Data Sourcementioning
confidence: 99%
“…1. Among the nine articles, four [20,22,32,33] were Caucasians, three [21,31,35] were from East Asian countries, one [34] was from India and one [14] was from Latin America. Because of the inadequate sample populations available for the Indian and Latin American group, we performed ethnicity-specific meta-analysis for Caucasian and East Asian populations.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…This combination of genes has also been implicated in the pathogenesis of other rheumatic diseases. In rheumatoid arthritis, the presence of KIR2DS2 was related to vasculitis [25]. Another study observed an association of KIR2DS2 in the absence of ligands of KIR2DL2 with increased risk of psoriatic arthritis [26].…”
Section: Systemic Sclerosis Cf (%)mentioning
confidence: 99%
“…KIR genotypes and HLA ligand patterns have been recognized for diseases and disease conditions such as hepatitis C [18], psoriasis vulgaris [19,20], psoriatic arthritis [21,22], rheumatoid arthritis [23], celiac disease [24], ulcerative colitis [25,26], Crohn's disease [27], human immunodeficiency virus [28], recurrent miscarriage [29], and leprosy [30], as well as in T1D [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%